2008
DOI: 10.1111/j.1600-051x.2008.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation at recombinant human bone morphogenetic protein‐2‐coated titanium implants in the posterior mandible (Type II bone) in dogs

Abstract: rhBMP-2 adsorbed onto TPO implant surfaces initiates dose-dependent peri-implant bone re-modelling resulting in the formation of normal, physiologic bone and clinically relevant osseointegration within 8 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 13 publications
9
75
0
2
Order By: Relevance
“…In our model, suboptimal BMP-2 doses were defined as lower than the ED 50 of 1.2 mg, while the optimal dose was determined as no higher than 5.0 mg due to a plateau effect using higher doses. Previous studies from our research group using canine 43,44 and non-human primate 45 models demonstrated that comparatively higher BMP-2 doses are associated with delayed bone maturation in craniofacial settings. This finding appears explained by an increased local inflammatory response to higher doses of BMP-2, also evidenced by frequent seroma formation 46 and increased remodeling/resorption rates of the adjoining resident bone.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our model, suboptimal BMP-2 doses were defined as lower than the ED 50 of 1.2 mg, while the optimal dose was determined as no higher than 5.0 mg due to a plateau effect using higher doses. Previous studies from our research group using canine 43,44 and non-human primate 45 models demonstrated that comparatively higher BMP-2 doses are associated with delayed bone maturation in craniofacial settings. This finding appears explained by an increased local inflammatory response to higher doses of BMP-2, also evidenced by frequent seroma formation 46 and increased remodeling/resorption rates of the adjoining resident bone.…”
Section: Discussionmentioning
confidence: 83%
“…This finding appears explained by an increased local inflammatory response to higher doses of BMP-2, also evidenced by frequent seroma formation 46 and increased remodeling/resorption rates of the adjoining resident bone. [43][44][45] Importantly, over longer healing intervals, bone maturation obscures these effects. It is noteworthy to point out that, based on the manufacturer's recommendations, our study only used *0.5%-10% BMP-2 per implant compared with that of the commercial product.…”
Section: Discussionmentioning
confidence: 99%
“…Wikesjo et al 10,19,37 X (***) X (*) 29. Wikesjo et al 10,19,37 X (***) X (*****) 30. Wikesjo et al 10,19,37 X (***) X (*)…”
Section: Study Characteristics and Descriptive Resultsunclassified
“…Schliephake et al 36 RGD Collagen 1 Dog Mandible 12. Schliephake et al 26 HA 10,19,37 BMP-2 Dog Mandible Table III shows 19 studies with its surface components, animal models, and implant location.…”
Section: Synthesis Of Meta-analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation